Taking stock and moving forward: A textual statistics approach to synthesizing four decades of job insecurity research. (November 2022) - Bazzoli, Andrea; Probst, Tahira M.
We collected the abstracts of manuscripts examining job insecurity published between 1984 and 2019 and carried out a textual analysis to investigate the defining clusters, their development over time, and whether there was evidence of siloed knowledge. Results suggested that job insecurity research seems to be fragmented into disciplinary foci (organizational psychology, public health, economics, and sociology). Further analyses on the organizational psychology corpus, revealed 25 topics with distinct temporal trajectories: some were increasing (analytical advances and differentiation between cognitive and affective job insecurity) while other were decreasing (scale development). The remaining abstracts revealed 15 topics with more stable trajectories. Based on these results, we identified five areas for future organizational research on job insecurity: the changing labor market, the need to better understand the experiences of marginalized workers and non-work outcomes of job insecurity, the added-value of qualitative research, and the need to critically evaluate our assumptions as researchers. Plain Language Summary : Since the paper by Greenhalgh and Rosenblatt, research on job insecurity has burgeoned. Taking an interdisciplinary perspective, we collected the abstracts of all peer-reviewed manuscripts examining job insecurity published between 1984 and 2019 and carried out a textual analysis using the Latent Dirichlet Allocation and the Reinert method to investigate (a) the defining clusters of job insecurity research, (b) the development of such clusters over time, and (c) whether there was any evidence of siloed knowledge. Results suggested that indeed job insecurity research seems to be fragmented into four main disciplinary foci (organizational psychology, public health, economics, and sociology) with relatively little cross-fertilization. We conducted further analyses of the abstracts stemming from organizational research on job insecurity, revealing 25 topics with distinct temporal trajectories (e.g., "hot" topics including the increasing use of advanced analytic techniques and differentiation between cognitive and affective job insecurity) and "cold" topics including the development of job insecurity measures). The remaining abstracts revealed 15 topics with more stable research interests over time (e.g., a continued reliance on appraisal theories). Based on these results, we identified five areas for future organizational research on job insecurity based on: the changing labor market, the need to better understand the experiences of marginalized workers and non-work outcomes of job insecurity, the added-value of qualitative research, and finally the need to critically evaluate our assumptions as researchers.